STIMULASI PENGENALAN HURUF MELALUI MEDIA PEMBELAJARAN LETTER DERMOLEN - Wati, Sindy Anugerah; Anggraini, Kristin; Takumansang, Regina Christine (Jurnal Abdimas Bina Bangsa, 2024)
Science can improve the welfare of society in order to build national civilization. Through science the quality of life of every human being increases. Knowledge can be obtained in various ways, one of which is through books. Books are needed by every individual to gain and increase knowledge. Gaining knowledge through books is done by reading. Reading is one way to understand all the information contained in the reading text to develop the reader's intellectual abilities. Considering the importance of reading for every individual's intellectual development, it is necessary to increase the culture of reading from an early age. The initial reading stage starts from recognizing letters, spelling vocabulary, reading words and reading sentences. The initial reading stage will feel more difficult or complicated because the child does not yet understand the sounds and symbols of letters. Difficulties or complications in reading need to be anticipated in various ways, one way that can be done is by using interesting media. This community service, Stimulating Letter Recognition through Letter Dermolen Learning Media, aims to stimulate language development, especially in letter recognition using Letter Dermolen media. Stimulation of letter recognition is carried out in every lesson to improve the reading skills of children aged 5-6 years old at Avicenna Kindergarten